Astronomy in the Islamic world: a European perspective - Kerner, Richard (Cadernos de Astronomia, 2024)
Mathematical and astronomical achievements of the Islamic World during its golden era are briefly exposed. The article is based on the invited talk delivered remotely at the ICRANET-Isfahan Astronomical meeting, November 2-5, 2021, which, in turn, reproduces major parts of one of the chapters of my book, Our Celestial Clockwork, published recently (2021) by the World Scientific
Keywords: history of science; astronomy; Islamic world